2016
DOI: 10.1007/s11368-016-1570-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of soils formed from biochemical ripening of dredged sediments—subsidence mitigation in delta areas

Abstract: Purpose In delta areas, dense networks of canals have been developed through time and have to be periodically dredged. Lowering the groundwater level in delta areas deepens the aerobic zone, leading to the oxidation of organic matter and possibly to land subsidence. The use of the dredged sediments on land can be a solution to mitigate land subsidence in delta areas. Materials and methods Five types of dredged sediments with different organic matter content and particle size distribution were dewatered for 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…This is also in line with previous observations on lab scale (Oliveira et al 2017) and meso-scale experiments (Oliveira et al 2018, In Press) using sediments dredged from the same location.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is also in line with previous observations on lab scale (Oliveira et al 2017) and meso-scale experiments (Oliveira et al 2018, In Press) using sediments dredged from the same location.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies with the same sediments have shown that the water retention capacity of the sediments dredged from the same location varies from 0.71 cm 3 water /cm 3 dry matter before ripening to 1.02 after ripening for a pF = 2 (Oliveira et al 2017), and the high water content can protect the organic matter from mineralization.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The soil physicochemical properties, the soybean aboveground and belowground biomass and yield, and the chemical composition of percolated solutions were investigated using a greenhouse approach. It is well established that high content of soil organic C increases soil fertility, soil stabilization, soil structure, water holding capacity, and crop productivity (Kögel‐Knabner & Rumpel, 2018; Newcomb et al., 2017; Oliveira et al., 2017). Studies have shown that average bulk density decreased with increasing dredged sediment ratios, allowing for better root penetration, increased water infiltration, higher porosity, and greater water holding capacity (Wang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%